The farm-gate methane intensity and blue water footprint of nine diverse beef cattle breeds in South Africa - N.T. Chabalala; M.C. Chadyiwa-Mokolobate; M.J. Mamabolo; N.O. Mapholi; M.M. Scholtz (South African Journal of Animal Science)
A simulation study was done to estimate the methane intensity and blue water footprint of a weaner calf production system in South Africa. Nine genotypes, representative of indigenous, British, Zebu, and European breeds, were chosen based on their relative numbers and the availability of data. A farm of 1200 ha with a carrying capacity of 6 ha/large stock unit (LSU), which could thus carry 200 LSU in total, was simulated. The enteric methane emission of an LSU was estimated to be 94 kg of methane/year (tier 2), implying that 18 800 kg of methane was produced per year by the farm (200 LSU × 94 kg of methane). Likewise, the litres of blue water consumed on the farm was 3285 kilolitres (200 LSU × 16 425 litres/year/LSU). The methane intensity (kg methane/kg live weight) was calculated by dividing the annual methane emissions of the farm by the total kilograms of live weight leaving the farm. The blue water footprint was estimated similarly. The total live weight leaving the farm was calculated by combining the total kilograms of saleable calves and the total kilograms of culled cows sold. The Afrikaner, Bonsmara, Angus, Brahman, and Brangus breeds had low methane intensities and blue water footprints, while the European breeds had high values. The methane intensity varied from 0.59 kg of methane to 0.85 kg of methane, a 44% difference. The water footprint varied from approximately 100 to 150 L/kg live weight leaving the farm. More research is needed to validate these differences.